Maternal Voice and Tactile Stimulation Modulate Oxytocin in Mothers of Hospitalized Preterm Infants: A Randomized Crossover Trial - Jessica Hirschel; Audrey Carlhan-Ledermann; Céline Ferraz; Laure-Anne Brand; Manuela Filippa; Edouard Gentaz; Fleur Lejeune; Olivier Baud (MDPI AG, 2023)
Prematurity is a major risk factor for perinatal stress and neonatal complications leading to systemic inflammation and abnormal mother-infant interactions. Oxytocin (OT) is a neuropeptide regulating the inflammatory response and promoting mother-infant bonding. The release of this hormone might be influenced by either vocal or tactile stimulation. The main objective of the current randomized, crossover, clinical trial was to assess the salivary OT/cortisol balance in mothers following the exposure of their baby born preterm to two types of sensorial interventions: maternal voice without or with contingent tactile stimulation provided by the mother to her infant. Among the 26 mothers enrolled, maternal voice intervention alone had no effect on OT and cortisol levels in the mothers, but when associated with tactile stimulation, it induced a significant increase in maternal saliva oxytocin (38.26 ± 30.26 pg/mL before vs 53.91 ± 48.84 pg/mL after, p = 0.02), particularly in the mothers who delivered a female neonate. Maternal voice intervention induced a significant reduction in cortisol and an increase in OT levels in mothers when the maternal voice with a tactile stimulation intervention was performed first. In conclusion, exposure to the maternal voice with a contingent tactile stimulation was associated with subtle changes in the maternal hormonal balance between OT and cortisol. These findings need to be confirmed in a larger sample size and may ultimately guide caregivers in providing the best intervention to reduce parental stress following preterm delivery.